Hydrothermal Synthesis and Crystal Structure of Thiophene-2,5-dicarboxylate Cadmium(II) - Zhao, Y.; Yang, Z. (Asian Journal of Chemistry, 2015)
One new cadmium compound using Cd(OAc)2·2H2O, thiophene-2,5-dicarboxylic acid with m.f. C16H26O15S2Cd2 has been successfully synthesized. The compound has been characterized by X-ray single-crystal diffraction and shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding.